Metodikkens skål! - Kjus, Audun; Kverndokk, Kyrre; Esborg, Line; Sem, Leiv (Tidsskrift for kulturforskning, 2016)
Moltke Moe, Norway's first professor of folklore, was an accomplished collector and he worked systematically with developing his collection techniques. Still, in-depth studies of Moe's fieldwork methodology have not been done. While previous studies of his collecting journeys have focused on the narrators and narratives, this article will shift the focus to the practical and ethical aspects of fieldwork. Our approach is to discuss Moe's efforts in light of one of the classic books of fieldwork methodology, Kenneth Goldstein's A Guide for field workers in folklore (1964). The article springs from an ongoing project about Moltke Moe's journeys for collecting medieval ballads in Western-Telemark in 1889-1891. The materials preserved from these journeys lie mainly in the Norwegian Folklore Archives. In addition to notebooks and journals, there are also letters and photographs. The aim here is primarily to use Goldstein's description of fieldwork methodology to structure and interpret the various archival remains from Moltke Moe's collection activities.